Systemizing a rural livelihood diversification framework for sustainable community-based agritourism: A participatory approach to ensure resilience - Cavalleri, Sofia Anna Enrica; Tanwattana, Puntita; Grünbühel, Clemens M. (Frontiers in Sustainable Food Systems, 2022)
Situated approaches of rural livelihood diversification, such as community-based agritourism, can localize sustainable food systems at the regional level. This research advances an integrated framework of indicators to assess the interdisciplinary benefits of rural livelihood diversification practices for sustainable local food systems and community resilience. We built a framework on four dimensions deducted from secondary data: (1) environmental, (2) sociocultural, (3) economic, and (4) health. These were validated with an inductive analysis of primary data, which we collected from a panel of experts with a content validity index and tested in three rural case studies with shadow observation and qualitative interviews. We conducted both in-depth interviews with community leaders (n = 10) and semi-structured interviews with multi-sectoral stakeholders (n = 40). Findings 1) identify a comprehensive list of indicators to assess environmental, sociocultural, economic, and health dimensions of rural livelihood diversification practices and 2) advance a participatory approach to prioritize indicators according to their regional relevance (co-developed with stakeholders involved in Bangkok’s local food systems). Food tourism connects the four dimensions by (1) preserving local agrobiodiversity (2) preserving rural communities’ traditions (3) creating new capacity building opportunities for community-driven socio-economic development and (4) recognizing the health benefits of indigenous foods. This study contributes to a value-added conceptualization of community-based agritourism as a rural livelihood diversification practice. Such research effort highlights the importance of co-producing and ground-truthing indicators for rural livelihood diversification practices localizing sustainable development goals.